Protocol investigating the clinical outcomes and cost-effectiveness of cognitive–behavioural therapy delivered remotely for unscheduled care users with health anxiety: randomised controlled trial. Issue 1 (January 2016) - Patel, Shireen; Malins, Sam; Guo, Boliang; James, Marilyn; Kai, Joe; Kaylor-Hughes, Catherine; Rowley, Emma; Simpson, Jayne; Smart, David; Stubley, Michelle; Tyrer, Helen; Morriss, Richard
Abstract : Background: Health anxiety and medically unexplained symptoms cost the National Health Service (NHS) an estimated £3 billion per year in unnecessary costs with little evidence of patient benefit. Effective treatment is rarely taken up due to issues such as stigma or previous negative experiences with mental health services. An approach to overcome this might be to offer remotely delivered psychological therapy, which can be just as effective as face-to-face therapy and may be more accessible and suitable. Aims: To investigate the clinical outcomes and cost-effectiveness of remotely delivered cognitive–behavioural therapy (CBT) to people with high health anxiety repeatedly accessing unscheduled care (trial registration: NCT02298036). Method: A multicentre randomised controlled trial (RCT) will be undertaken in primary and secondary care providers of unscheduled care across the East Midlands. One hundred and forty-four eligible participants will be equally randomised to receive either remote CBT (6–12 sessions) or treatment as usual (TAU). Two doctoral research studies will investigate the barriers and facilitators to delivering the intervention and the factors contributing to the optimisation of therapeutic outcome. Results: This trial will be the first to test the clinical outcomes and cost-effectiveness of remotely delivered CBT for the treatment of high health anxiety. Conclusions: The findings will enable an understanding as to how this intervention might fit into a wider care pathway to enhance patient experience of care.